PENERAPAN FUNGSI MANAJEMEN DAKWAH DALAM MENINGKATKAN KUALITAS AKHLAKUL KARIMAH ANAK ASUH DI PANTI ASUHAN MAMIYAI YAYASAN AMAL DAN SOSIAL KECAMATAN MEDAN AREA KOTA MEDAN - M Ichwanurrahman; Syukur Kholil (Jurnal Bilqolam Pendidikan Islam, 2025)
This study aims to describe the implementation of dakwah management functions in fostering the moral character (akhlaq al-karimah) of foster children at Mamiyai Orphanage, as well as to identify supporting and inhibiting factors. Using a qualitative field research approach involving interviews, observation, and documentation, the study found that management functions—planning, organizing, directing, supervising, and evaluating—were systematically applied. Dakwah activities such as routine worship practices, moral guidance, and involvement in social activities effectively contributed to character development. While adequate facilities and community support served as strengths, challenges such as low learning motivation among children and the negative influence of digital technology emerged as obstacles in the characterbuilding process